FAO fisheries technical paper N.350.1 - FAO (FAO, 1995)
Document proposes a definition of the precautionary approach to fisheries as well as an elaboration on the burden of proof. It also contains detailed guidelines on how to conduct fishery management and research and how to develop and tranfer fishery technology in a context of uncertainty and responsible fisheries. Guidelines are also provided on species introduction, voluntary or accidental ( including through ballast water and sediment discharge ), recognizing the difficulty of ensuring a precautionary approach in relation to that issue. The guidelines are aimed at the governments, fisheries authorities, fishery industry, regional fishery management bodies.